2023
DOI: 10.3389/fvets.2022.1057977
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of RNA viruses of three dominant tick species in North China

Abstract: BackgroundA wide range of bacterial pathogens have been identified in ticks, yet the diversity of viruses in ticks is largely unexplored.MethodsHere, we used metagenomic sequencing to characterize the diverse viromes in three principal tick species associated with pathogens, Haemaphysalis concinna, Dermacentor silvarum, and Ixodes persulcatus, in North China.ResultsA total of 28 RNA viruses were identified and belonged to more than 12 viral families, including single-stranded positive-sense RNA viruses (Flaviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…The most abundant viral order recovered in our data, the Monogenavirales, are a large group of nonsegmented, enveloped viruses currently classified into 11 families and infecting a broad diversity of plants, animals, humans, and frequently reported from metatranscriptomic tick surveys [37,56,57]. All nine tick genomes analyzed here contained EVEs of mononegavirus provenance (n = 208), with a majority from the family Rhabdoviridae (n = 186; 89.4%).…”
Section: Mononegavirales (-Ssrna)mentioning
confidence: 82%
“…The most abundant viral order recovered in our data, the Monogenavirales, are a large group of nonsegmented, enveloped viruses currently classified into 11 families and infecting a broad diversity of plants, animals, humans, and frequently reported from metatranscriptomic tick surveys [37,56,57]. All nine tick genomes analyzed here contained EVEs of mononegavirus provenance (n = 208), with a majority from the family Rhabdoviridae (n = 186; 89.4%).…”
Section: Mononegavirales (-Ssrna)mentioning
confidence: 82%
“…It is genetically related to SFTSV and Heartland virus by phylogenetic analyses and may have a similar RNA replication mechanism to SFTSV ( Shen et al, 2018 ). Mukawa virus (MKWV) was first detected in I. persulcatus in Japan in 2018, and researchers found that I. persulcatus and H. concinna in Heilongjiang Province carried MKWV and were capable of infecting mammals, but it had not yet been reported in other countries or regions ( Wang et al, 2022 ; Qin et al, 2023 ). It was curious that MKWV was not genetically similar to any other tick-borne Phenuiviridae viruses on the phylogenetic tree, instead, it was related to viruses transmitted by mosquitoes and sandflies ( Matsuno et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…As another member of the genus Bandavirus, GTV is a new tick-borne Bandavirus detected in 2018 from D. nuttalli and human serum samples in XUAR. It is genetically related to SFTSV and Heartland virus by phylogenetic analyses and may have a similar RNA replication mechanism to SFTSV (Shen et al, 10.3389/fmicb.2024.1309698 Frontiers in Microbiology 04 frontiersin.org (Wang et al, 2022;Qin et al, 2023). It was curious that MKWV was not genetically similar to any other tick-borne Phenuiviridae viruses on the phylogenetic tree, instead, it was related to viruses transmitted by mosquitoes and sandflies (Matsuno et al, 2018).…”
Section: Phenuiviridaementioning
confidence: 99%
“…Furthermore, I. persulcatus has been identified as a carrier of viruses from at least seven different virus families, including Peribunyaviridae , Nairoviridae , Orthomyxoviridae , Phenuiviridae , Reoviridae , Flaviviridae , and Phenuiviridae [ 4 , 5 ]. Some of these viruses, such as TBEV and Powassan virus (POWV), are closely associated with human diseases.…”
Section: Introductionmentioning
confidence: 99%